THE IMPACT OF DIET ON RHEUMATOID ARTHRITIS (RA) TREATMENT AND ACTIVITY - Agnieszka Bajkacz; Izabela Polakowska; Agnieszka Roszyk; Kamil Orczyk; Alicja Dankowska; Małgorzata Zielonka; Zuzanna Głowacka; Jakub Białek; Patrycja Stygar; Agata Bęben (International Journal of Innovative Technologies in Social Science, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation, destructive changes, and numerous systemic complications. Treatment is based on disease-modifying antirheumatic drugs (DMARDs) and biological therapies. In recent years, increasing attention has been paid to the impact of diet on the risk of developing RA and disease activity, as well as the role of diet as an adjunctive therapy in the treatment of RA. Many studies indicate that an appropriately selected diet can modulate the inflammatory response, affect the gut microbiota and the overall clinical condition of patients with RA. We analyse publications from 2018–2025, including observational studies, randomized controlled trials (RCTs) and systematic reviews on the role of diet in RA. We discuss the effect of selected types of anti-inflammatory diets and omega-3 fatty acids, fiber, polyphenols, and vitamin D in patients with RA. We highlight also the role of the gut microbiota in RA. Aim of this study: The objective of this study is to summarise the latest reports on how diet and its components impact RA activity and treatment. Materials and methods: A literature review was conducted using the professional PubMed database. Articles published between 2018 and 2025 were included. The searches included combinations of the following keywords: “rheumatoid arthritis,” “diet,” “anti-inflammatory diet,” “omega-3 fatty acids,” “fiber” and “polyphenols”.